A MYB-related transcription factor from peanut, AhMYB30, improves freezing and salt stress tolerance in transgenic Arabidopsis through both DREB/CBF and ABA-signaling pathways - Chen, Na; Pan, Lijuan; Yang, Zhen; Su, Maowen; Xu, Jing; Jiang, Xiao; Yin, Xiangzhen; Wang, Tong; Wan, Feifei; Chi, Xiaoyuan (Frontiers in Plant Science, 2023)
Abiotic stresses such as salinity and low temperature have serious impact on peanut growth and yield. The present work investigated the function of a MYB-related transcription factor gene AhMYB30 obtained from peanut under salt and low temperature stresses. The results indicated that the overexpression of AhMYB30 in Arabidopsis could enhance the resistance of transgenic plants to freezing and salt stresses. The expression of stress-response genes RD29A (Response-to-Dehydration 29A), COR15A (Cold-Regulated 15A), KIN1 (Kinesin 1) and ABI2 (Abscisic acid Insensitive 2) increased in transgenic plants compared with in wild-type, while there was no significant difference in the transcript level of CBF1-3 (C-repeat Binding Factor 1-3). Subcellular localization and transcriptional autoactivation validation demonstrated that AhMYB30 has essential features of transcription factors. Therefore, AhMYB30 may increase salt and freezing stress tolerance as the transcription factor (TF) in Arabidopsis. Our results lay the theoretical foundation for exploring stress resistance mechanisms of peanut and offering novel genetic resources for molecular breeding.